(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This literature review examines the typological divergence in temporal encoding between Uzbek (Turkic, agglutinative, SOV) and English (Germanic, analytic, SVO). Uzbek employs morphologically dense verbal suffixes (-di, -gan, -yap) that fuse Tense, Aspect, Modality, and Evidentiality (TAM-E), while English relies on periphrastic constructions and auxiliary verbs within a binary tense system. Both languages utilize spatial metaphors for temporal conceptualization, yet their structural differences generate distinct discourse patterns and substantial challenges for translation and second language acquisition. The review advocates for corpus-based research to quantify pragmatic realizations of these typological contrasts.